A STRATEGI PENGEMBANGAN DAN KELAYAKAN BISNIS PADA CV SAHABAT TERNAK KABUPATEN SLEMAN YOGYAKARTA - Doni Sahat Tua Manalu; Syaharani (Politeknik Pembangunan Pertanian Medan, 2020)
Goat milk soap is a solution for consumers of the dangers of using chemical based soaps for skin health. Processed products in the form of organic soap made from goat's milk are currently being developed to be an alternative business in increasing the income of goat breeders, especially at CV Sahabat Ternak. The purpose of this study is to analyze the development strategy and business feasibility of CV Sahabat Ternak. The research was carried out at CV Sahabat Ternak, Sleman Regency, Yogyakarta in March-April 2020, the research location was chosen purposely to collect primary data through questionnaires and interviews, then secondary data was obtained from various literatures. Data analysis was performed using a SWOT matrix, then business feasibility analysis by calculating NPV, Gross B/C, Net B/C, IRR and Payback Period. The results showed that the strategy that can be implemented is to use the S-O strategy (Strengths-Opportunities), namely strength by taking advantage of opportunities. From the results of the analysis of the company's financial planning, it is feasible because it fulfills the eligibility criteria for investment with an NPV value of IDR 78,026,606.61, Gross B/C> 1, Net B/C 5, IRR 97%, and Payback Period for one year and one month.